Insulin-like growth factor axis genetic score and sports excellence - Ben-Zaken, S.; Meckel, Y.; Nemet, D.; Eliakim, A. (The Journal of Strength and Conditioning Research, 2021)
It has been suggested that IGF1 polymorphisms associated with circulating IGF1 levels may be linked to elite short-distance running performance. This study assessed genetic score based on 6 polymorphisms related to the Insulin-like growth factor axis (rs7136446, rs35767, rs6220, rs680, rs2854744, and rs1805086) among elite Israeli runners and swimmers. One hundred sixty-one track and field athletes (123 men and 38 women, age 17-50 years) and 94 swimmers (61 men and 33 women, age 16-49 years) participated in the study. Athletes were divided into short-distance runners (SDRs, major event: 100-200-m sprints and jumps, n = 63) and long-distance runners (LDRs, major event: 5,000 m and marathon, n = 98). Swimmers were divided into short-distance swimmers (SDSs, major event: 50-100 m, n = 44) and long-distance swimmers (LDSs, major event: 400-1,500 m, n = 50). Groups were subdivided into top-level and national-level athletes. We calculated the IGF genetic score (IGF-GS) of all the subjects on a 0-100 scale. Top-level SDRs' mean IGF-GS (30.8 ± 11.7) was significantly higher (p < 0.006) compared with national-level SDRs' (20.5 ± 11.3) and top-level SDSs' (19.9 ± 8.5). Subjects with IGF-GS >25 had an increased odds ratio (OR) of being elite-level SDRs (OR: 4.2; 95% confidence interval: 0.68-26.09; p < 0.001). In summary, a combined assessment of 6 single-nucleotide polymorphisms, all known to modulate circulation IGF1 levels, was associated with a higher genetic score among SDRs, emphasizing the importance of the IGF system to land speed sports events but not to swimming events. Whether the IGF-GS may be used for selection of elite-level sprinters in early stages of their athletic career needs to be further investigated.